STRATEGIC PROFILING: EMPIRICAL EVIDENCE OF SUPPLY CHAIN STRATEGY PRACTICES IN SMALL AND MEDIUM ENTERPRISES - Titik Kusmantini; Wisnu Untoro (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: The purpose of this study is to describe the characteristics of the development pattern of the capabilities of SME (Small and Medium Enterprises) to manage an integrated supply chain’s capabilities. Background Problems: The use of a single source will lead to a single respondent bias and give rise to inter-rater reliability for the perceptual data. When measuring the performance variables in this study, which uses self-reporting, the use of a single respondent will lead to bias. Novelty: This study aims to test the concept of fit, in particular for the alignment of strategy between functions, which are the supply chain and manufacturing strategies, by using a selection approach. The taxonomy result will produce a strategic profile which is able to describe the extent to which the strategic decision agrees with, and is consistent between the functions of SMEs in particular. Research Methods: The hypothesis testing process of the study uses a sample of 102 SMEs in the Province of Yogyakarta, Indonesia. The testing technique used in this study is a cluster analysis and an ANOVA. Findings/Results: The testing result of the cluster analysis identifies three taxa of supply chain strategy groups. The result of the ANOVA test is used to test three hypotheses and all the hypotheses are supported, while the hypothesis of the supply chain’s strategy group differences, based on the type of product, is not proven. Conclusion: The cluster testing result produces strategic profiling; it identifies the three groups of the supply chain’s strategies that describe the ability of SMEs to design their supply chain’s capabilities, with particular regard to the six dimensions of the supply chain’s strategy that have been listed.